Impact of left ventricular fibrosis and longitudinal systolic strain on outcomes in low gradient aortic stenosis. (14th October 2021) - Fukui, M; Annabi, M S; Rosa, V E E; Ribeiro, H B; Tarasoutchi, F; Shelbert, E B; Bergler-Klein, J; Mascherbauer, J; Rochitte, C E; Pibarot, P; Cavalcante, J L
Abstract: Background: The clinical utility of comprehensive cardiac magnetic resonance (CMR) for the assessment of myocardial structure and function remains unknown in patients with low gradient (LG) aortic stenosis (AS). Purpose: This study sought to compare CMR characteristics of myocardial structure and function according to different flow / gradient patterns of AS: classical low flow LG (LFLG); paradoxical LFLG; normal flow LG; and high gradient, and to evaluate their impact on the outcomes of these patients. Methods: International multicentric prospective study included 147 patients with LG moderate to severe AS and 18 patients with high gradient severe AS who underwent comprehensive CMR evaluation of left ventricular global longitudinal strain (LVGLS), extracellular volume fraction (ECV), and late gadolinium enhancement (LGE). Results: Patients with classical LFLG (n=90) had more LV adverse remodeling and impaired longitudinal function including higher ECV, and higher LGE and volume, and worst LVGLS, compared to other patterns of AS. Over a median follow-up of 2-years, 43 deaths and 48 composite outcomes of death or heart failure hospitalization occurred in LG AS patients. As LVGLS or ECV worsened, risks of adverse events also increased (per tertile of LVGLS: HR [95% CI] for mortality, 1.50 [1.02–2.20]; p=0.04; HR [95% CI] for composite outcome, 1.45 [1.01–2.09]; p<0.05) (per tertile of ECV: HR [95% CI] for mortality, 1.63 [1.07–2.49]; p=0.02; HR [95% CI] for composite outcome, 1.54 [1.02–2.33]; p=0.04). LGE presence was also associated with higher mortality (HR [95% CI], 2.27 [1.01–5.11]; p<0.05) and risk of the composite outcome (HR [95% CI], 3.00 [1.16–7.73]; p=0.02). The risk of all-cause death and of the composite outcome increased in proportion to the number of impaired components (i.e. LVGLS, ECV and LGE) (Figure) with and without adjustment for age, true severe AS, classical LFLG, and aortic valve replacement as a time-varying covariate. Conclusions: In this international multicentric study of LG AS, comprehensive CMR assessment of myocardial structure and function provides independent prognostic value that is cumulative and incremental to clinical and echocardiographic characteristics. Funding Acknowledgement: Type of funding sources: None.